KB Acceptors Inject 3 Months With Compliance Repeat Visits at Mogang Health Center, Samosir Regency - Nurhamida Fithri; Junita Manullang; Faradita Wahyuni (Pena Cendekia Insani, 2022)
Objectives: Injectable contraception for 3 months is Depo Medroxyprogesterone Acetate (Depoprovera), containing 150 mg of DMPA. Given every 3 months by injection intramuscularly (IM) in the buttocks area. Motivation has a very important role because with motivation it can be expected that every employee has the desire to work hard to achieve the results achieved with high overall resources used. This study aims to determine the relationship between knowledge and motivation with follow-up visits at Mogang Health Center, Samosir Regency. Method: This study used a cross-sectional design. The population in this study were all family planning acceptors who visited the Mogang Health Center, Samosir Regency from January to March 2022 as many as 80 people. And a sample of 45 people. Data analysis using chi square test. Result: The results showed that there was a correlation between the motivation of 3 months injection family planning acceptors and the adherence to repeat visits (p = 0.000). The results showed that of the 25 injection family planning acceptors who had positive motivation, there were 18 people (40%) who were obedient to the repeat visits and 7 people (15.46%) who were not obedient to the repeat visits. Of the 20 injection family planning acceptors who had negative motivation, there were 20 people (44.44%) who did not comply with the repeat visit. Conclusion: From the results of the study, it can be concluded that there is a relationship between the motivation of 3 months injection family planning acceptors and the compliance of repeat visits at the Mogang Health Center, Samosir Regency.